PENGARUH KONSEP DIRI DAN KEBIASAAN BELAJAR TERHADAP HASIL BELAJAR SISWA KELAS X MATA PELAJARAN EKONOMI JURUSAN ADMINISTRASI PERKANTORAN SEKOLAH MENENGAH KEJURUAN LAB BUSINESS SCHOOL TANGERANG - dede kurniasih; femi handayani; Estu Niana Syamiya (Universitas Islam Syekh Yusuf, 2020)
AbstractThe purpose of this study was to determine the effect of self-concept and study habits on student learning outcomes. The research method used is descriptive quantitative method with multiple linear regression data analysis techniques. The sample in this study was 62 students of class X SMK office administration who were taken using probability simple random sampling with data collection using google form. Based on the results of the calculation, the regression equation is Y = 2.922 + 0.224 + 0.355, with an F test value of 0.000 so that it can be interpreted that simultaneously self-concept and study habits have an effect on learning outcomes. The results of this study indicate the magnitude of the influence of self-concept and study habits on student learning outcomes of class X office administration is 68.3%.Keywords: Self Concept, Study Habits, Learning Outcomes